2007
DOI: 10.1016/j.ememar.2006.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Real exchange rates, dollarization and industrial employment in Latin America

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0
6

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 25 publications
0
19
0
6
Order By: Relevance
“…In these studies, employment fluctuations are found to be significantly related to RER movements and volatility in high income OECD and the European Union countries (Burgess and Knetter, 1998;Gourinchas, 1998Gourinchas, , 1999Goldberg et al, 1999;Campa and Goldberg, 2001;Belke and Gros, 2002;Belke and Setzer, 2003;Klein et al, 2003 Galindo et al (2006) show that RER depreciations have negative employment effects in industries with high liability dollarization. None of these studies, however, focus directly on the employment effects of exchange rate volatility in developing countries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In these studies, employment fluctuations are found to be significantly related to RER movements and volatility in high income OECD and the European Union countries (Burgess and Knetter, 1998;Gourinchas, 1998Gourinchas, , 1999Goldberg et al, 1999;Campa and Goldberg, 2001;Belke and Gros, 2002;Belke and Setzer, 2003;Klein et al, 2003 Galindo et al (2006) show that RER depreciations have negative employment effects in industries with high liability dollarization. None of these studies, however, focus directly on the employment effects of exchange rate volatility in developing countries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, Galindo et al (2007) shares the same deficiency with Edwards (1989b), namely that real wages or labor shares in GDP or employment are not direct proxies for the income distribution or inequality. One may raise a concern about how well these proxies are able to represent the income distribution across the total population, sectors or countries.…”
Section: Literature Reviewmentioning
confidence: 95%
“…The limitation, however, can be mitigated once we collect appropriate data and employs regression analysis with control variables. Galindo et al (2007) look at the effects of real depreciations on industrial employment. Using a panel dataset on industrial employment and trade for nine Latin American countries, they conclude that real depreciations impact employment growth positively in countries with high trade openness (Note 8).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Haltiwanger and others (2004), meanwhile, have found a positive relationship between net job creation and real-term currency appreciation. Lastly, Galindo, Izquierdo and Montero (2007), working with disaggregated industrial data, have observed that real-term depreciation tends to raise employment in industries with low levels of dollar borrowings and reduce it in industries with heavy foreign currency borrowings. 10…”
Section: Trade and Employmentmentioning
confidence: 99%